Synergistic inhibition of gastric cancer cell proliferation by concanavalin A and silibinin via attenuation of the JAK/STAT3 signaling pathway and molecular docking analysis - Gaoyan Hua; Lisha Zhao; Xianjing Zeng; Liang Luo (Hereditas)
Abstract Background In the current period of pharmaceutical discovery, herbal remedies have shown to be an unmatched supply of anticancer medications. Plants and their derivatives, through analogues, play a vital role in cancer treatment. Objectives The current investigation assessed the effectiveness of inhibiting the growth of gastric cancer cells in AGS cells by blocking the JAK/ STAT3 signalling pathways using the natural medicines Concanavalin A (Con-A) and silibinin (SB). Materials and methods After being exposed to various doses of concanavalin A, and silibinin (Con-A + SB) for 24 h (0- 60 µM), the cells were evaluated for multiple studies. The MTT assay was used to examine the combination of Con-A + SB-induced cytotoxicity. To evaluate ROS, DCFH-DA staining was utilized. Dual (AO/EtBr) staining was performed to examine apoptotic modifications, and MMP levels in AGS cells were examined using the appropriate fluorescence staining assays. By using flow cytometry and western blotting, cell cycle, and apoptosis were assessed. Results The relative cytotoxicity of Con-A and SB was found to be approximately 19.6 μM and 16.78 μM, (p < 0.05) correspondingly, according to the findings. After a 24-h incubation period, the combination of Con-A and SB generates significant cytotoxicity in AGS cells, with an IC50 of 10.37 μM (p < 0.01). Furthermore, AGS cells treated with Con-A and SB concurrently showed increased apoptotic signals, exhibited by Bax overexpression, Bcl-2 downregulation, and Caspase-3 activation, as well as considerable ROS generation. Conclusion Therefore, the combination usage of Con-A + SB has the potential to serve as a chemotherapeutic agent since it prevents the synthesis of JAK/STAT3 intermediated control of proliferation and cell cycle-regulating proteins.